2018
DOI: 10.1007/s00125-018-4699-7
|View full text |Cite
|
Sign up to set email alerts
|

Human fetoplacental arterial and venous endothelial cells are differentially programmed by gestational diabetes mellitus, resulting in cell-specific barrier function changes

Abstract: Aims/hypothesisAn adverse intrauterine environment can result in permanent changes in the physiology of the offspring and predispose to diseases in adulthood. One such exposure, gestational diabetes mellitus (GDM), has been linked to development of metabolic disorders and cardiovascular disease in offspring. Epigenetic variation, including DNA methylation, is recognised as a leading mechanism underpinning fetal programming and we hypothesised that this plays a key role in fetoplacental endothelial dysfunction … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
25
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(27 citation statements)
references
References 52 publications
1
25
0
Order By: Relevance
“…Previous research has only focused on the effects of miRNAs or mRNAs in GDM on the heart development of offspring, without a comprehensive analysis of the miRNA-mRNA axis [28][29][30]. Strutz J [13] and Cvitic S [14] analyzed the changes in the expression of miRNAs and mRNAs in dAECs of GDM and concluded that these changes would increase the risk of longterm cardiovascular disease in the offspring. However, the study did not further clarify and verify whether these miRNAs and mRNAs were involved in the development of the heart during the embryonic stage.…”
Section: Discussionmentioning
confidence: 99%
“…Previous research has only focused on the effects of miRNAs or mRNAs in GDM on the heart development of offspring, without a comprehensive analysis of the miRNA-mRNA axis [28][29][30]. Strutz J [13] and Cvitic S [14] analyzed the changes in the expression of miRNAs and mRNAs in dAECs of GDM and concluded that these changes would increase the risk of longterm cardiovascular disease in the offspring. However, the study did not further clarify and verify whether these miRNAs and mRNAs were involved in the development of the heart during the embryonic stage.…”
Section: Discussionmentioning
confidence: 99%
“…Placentas from mothers with HIP are frequently larger, with an increased placental weight and placental-weight to birth-weight ratio irrespective of glycemic control (25). Epigenetic studies of Genome-wide methylation analysis highlighted that metabolic disturbances associated to Gestational Diabetes (GDM) may also affect DNA methylation and gene expression profile, particularly at arterial (AEC) and venous endothelial cells (VEC) level, with respect to cell morphology, cellular movement, and those inducing actin organisation and barrier functions (26).…”
Section: Placenta: a Metabolic Organmentioning
confidence: 99%
“…The exposure to GDM programs atypical barrier function and morphology in fetoplacental endothelial cells by methylation of DNA and gene expression change. The effects were different in AEC and VEC and indicated a stringent cell-specific sensitivity to affected exposure-linked developmental programming in utero [ 63 ].…”
Section: Epigenetics In Gdmmentioning
confidence: 99%